Upgrading of sewage sludge by low temperature pyrolysis: Biochar fuel properties and combustion behavior. (15th September 2021) - Chen, Renjie; Sheng, Qian; Dai, Xiaohu; Dong, Bin
Graphical abstract: Highlights: The low temperature pyrolysis of sewage sludge process is developed. Biochar as a solid fuel with less nitrogen and sulfur content. The first order combustion reaction of biochar is derived. The combustion behavior of biochar is easier and more stable. Abstract: The co-incineration of sewage sludge (SS) in thermal power plants offers a promising method of sustainable waste handling for China due to its large-scale capacity and high compliance with pollutant emission control regulations. However, conventional co-incineration treatment of SS has unstable combustion performance and a lower blending ratio due to the high moisture content and complex components of SS. To overcome this drawback, the low-temperature pyrolysis (LTP) process has been used to upgrade the fuel properties of SS. In this study, different pyrolysis temperatures (300–500 °C) were employed to convert SS to clean solid fuel and the biochar properties and combustion behaviors were evaluated. The results showed that when the pyrolysis temperature was <400 °C, 50–60% of the energy in the raw sludge (RS) was converted into biochar. Analysis of the fuel properties showed that the fuel ratio of the biochar was significantly increased to 0.54 and the H/C and O/C atomic ratios reduced to 0.76 and 0.33 by prolonging the pyrolysis process. Moreover, around 70% nitrogen and sulfur were removed. The thermogravimetric analysis showed that the combustion decomposition was altered from devolatilization and combustion for RS to char combustion for biochar. The combustion reaction of RS and biochar were best fitted to the first-order. The combustion behaviors of biochar were less violent and more stable than those of RS due to the lower activation energy and frequency factor in the pyrolysis temperature range of 300–350 °C.